Propolis in Human Health: Unraveling Chemistry, Applications, and Efficacy - Jakub Ptak; Marek Miśkiewicz; Rafał Noga; Jagoda Marcinkowska; Adrian Herc; Karolina Koczkodon; Victoria Teska; Jakub Perłowski; Marcelina Sawczuk; Mariusz Krompiewski (Nicolaus Copernicus University in Toruń, 2024)
The paper explores the diverse aspects of propolis, a resinous substance created by bees from botanical sources, presenting a comprehensive overview of its chemistry, applications, and efficacy in human health. Propolis, colloquially known as "bee glue," serves as a versatile material in hive construction and defense against diseases and predators. Its chemical composition, influenced by geographic origins, comprises a myriad of bioactive compounds, including flavonoids, phenolic acids, terpenoids, and more. The study delves into the pharmacological activities of propolis, emphasizing its antioxidant, antimicrobial, anti-inflammatory, and anticancer properties. Propolis exhibits a direct correlation between its biological activity and the quality of its chemical constituents. The antioxidant activity, attributed to flavonoids, plays a crucial role in mitigating oxidative stress and associated chronic inflammation. Furthermore, the paper discusses the therapeutic potential of propolis in various health conditions, such as diabetes mellitus, cardiovascular diseases, asthma, COPD, and wound healing. In diabetes, propolis shows promise in reducing blood glucose levels and insulin resistance. Its cardioprotective effects are linked to antioxidant compounds, addressing oxidative stress in cardiovascular diseases. Propolis demonstrates anti-allergic and anti-inflammatory effects in respiratory conditions, providing potential relief for asthma and COPD patients. Additionally, propolis accelerates wound healing through its immunomodulatory, antimicrobial, and antioxidant properties. In conclusion, propolis emerges as a natural resource with significant potential for human health, presenting a diverse array of bioactive compounds that contribute to its therapeutic efficacy across various medical conditions. The multifaceted nature of propolis makes it a subject of growing interest for further research and exploration in the field of medicine and healthcare.